ALTERNATIVE MODEL OF CARBON CONNECTION OF DIAMOND - Ilya Evgenievich Eremin; Eugenia Aleksandrovna Podolko (Наука. Инновации. Технологии)
Carbon materials especially interesting for practical application in the different areas of science and technique, by virtue of the numerous unique physical and chemical properties. The popular object of researches presently is allotropic modification of carbon - diamond that is examined as a classic model crystal. One of the most effective going near research of physical and chemical properties of diamond is his study by means of preliminary computer design of the studied dielectric descriptions. The authors of the article examine the traditional and alternative mathematical models of electronic configuration of non-polar valency chemical connection of diamond. Results over of design of dielectric descriptions of resilient electronic polarization of the examined material are brought on the basis of an offer physical interpretation of electronic structure.